Leading Youth to Spiritual and Cultural Perfection - The Main Task of The Development of New Uzbekistan - Rasulova Marifat Madazimovna (Scientific Trends, 2025)
This article analyzes the issue of forming the spiritual and cultural perfection of youth in the process of the development of New Uzbekistan. It highlights the spiritual outlook of the younger generation, cultural growth, and ensuring the harmony of national and universal values as one of the priority areas of state policy. Also, the mutual cooperation of educational, cultural, family, and neighborhood institutions in raising young people as perfect people is scientifically substantiated.
Keywords: New Uzbekistan, spirituality, culture, youth, values, upbringing, national revival, perfection, education system.